Chronic wasting disease management in ranched elk using rectal biopsy testing. Issue 2 (4th March 2018) - Haley, Nicholas J.; Henderson, Davin M.; Wyckoff, Sara; Tennant, Joanne; Hoover, Edward A.; Love, Dan; Kline, Ed; Lehmkuhl, Aaron; Thomsen, Bruce
ABSTRACT: Chronic wasting disease (CWD) is a transmissible spongiform encephalopathy (TSE) affecting members of the cervid species, and is one of the few TSEs with an expanding geographic range. Diagnostic limitations, efficient transmission, and the movement of infected animals are important contributing factors in the ongoing spread of disease. Managing CWD in affected populations has proven difficult, relying on population reduction in the case of wild deer and elk, or quarantine and depopulation in farmed cervids. In the present study, we evaluated the effectiveness of managing endemic CWD in a closed elk herd using antemortem sampling combined with both conventional and experimental diagnostic testing, and selective, targeted culling of infected animals. We hypothesized that the real-time quaking-induced conversion (RT-QuIC) assay, a developing amplification assay, would offer greater detection capabilities over immunohistochemistry (IHC) in the identification of infected animals using recto-anal mucosa associated lymphoid tissue (RAMALT). We further sought to develop a better understanding of CWD epidemiology in elk with various PRNP alleles, and predicted that CWD prevalence would decrease with targeted culling. We found that RT-QuIC identified significantly more CWD-positive animals than IHC using RAMALT tissues (121 vs. 86, respectively, out of 553 unique animals), and that longstanding disease presence was associated with an increasing frequency of less susceptible PRNP alleles. Prevalence of CWD increased significantly over the first two years of the study, implying that refinements in our management strategy are necessary to reduce the prevalence of CWD in this herd.